Paracingulate sulcus asymmetry; sex difference, correlation with semantic fluency and change over time in adolescent onset psychosis. - Clark, G; Mackay, C; Davidson, M; Iversen, S; Collinson, S; James, A; Roberts, N; Crow, T (2010)
The left paracingulate sulcus (PCS) is longer than the right and the adjacent cortex is activated by the generation of words. In adult patients with chronic schizophrenia the anatomical asymmetry is reduced. In 35 controls and 38 adolescents with schizophrenia or schizoaffective disorder (mean age = 16 years) we found that semantic verbal fluency correlated with leftward PCS asymmetry in controls but not in patients. At intake, PCS length did not differ between patients and controls, but at follow-up (13 controls, 10 patients, mean age = 18 years) PCS asymmetry (comprising both increasing left and decreasing right length) increased significantly, the increase was greater in males than in females, and there was a trend for a diagnosis * sex * side * time interaction such that in controls leftward PCS asymmetry increased, while in patients of both sexes there was convergence toward symmetry. Thus sulcal anatomy develops differentially in the two sexes during adolescence, and the pattern of asymmetric sex-dependent change over time may distinguish patients with psychosis from controls. Greater change in asymmetry during adolescence may explain earlier age of onset in males and greater deficits in verbal fluency.